Academic Resilience in Final Year Students Viewed from Spiritual Intelligence - Sandri, Ritna; Siagian, Yosua Alberto (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
Abstract :This study aims to determine the influence of spiritual intelligence on academic resilience in final-year students. This research uses a quantitative correlational method, with a total of 100 respondents. The sampling technique employed is accidental sampling. Data collection was done using the Academic Resilience Scale (48 items, α = 0.916) and the Spiritual Intelligence Scale (27 items, α = 0.927). The data analysis used simple regression analysis, which resulted in a correlation coefficient of 0.244 with p = <0.001 (p < 0.005). This indicates that spiritual intelligence has a significant impact on academic resilience in final-year students. Spiritual intelligence contributes effectively by 24.4% to academic resilience. This research can serve as a foundation for the development of programs aimed at improving spiritual intelligence and academic resilience, particularly for final-year students who are facing academic pressures.Keywords: spiritual intelligence, academic resilience